(untitled) (Journal of Universal Science Research, 2025)
Virology is a branch of microbiology that studies the structure, properties, reproduction, and pathogenicity of viruses. Viruses occupy a special place among infectious agents, as they represent non-cellular forms of life capable of reproducing only inside living cells. Understanding the structure, chemical composition, and mechanisms of viral replication is essential for the diagnosis, prevention, and treatment of viral infections